2011
DOI: 10.4028/www.scientific.net/kem.462-463.894
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility Analysis of the Welded Metal Bellows of Mechanical Seal

Abstract: In this study, the stiffness and the flexibility of welded metal bellows of mechanical seal is studied numerically by changing the number of bellows membrane and the loading condition. The relationship between the number of membrane and the displacement, the stress and the flexibility are analyzed. For further improved the axial displacement, overall stiffness and the flexibility of the welded metal bellows membrane, the finite element analysis are conducted. The numerical results show that the maximum stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…M. Hamada [6] obtained information on the design of bellows through experimental studies and gave the appropriate design criteria. Mamtimin Geni [7] used a 1/4 finite element model based on the symmetry of the bellows and analyzed it under different numbers of diaphragm sets and loading conditions. K. Tsukimori [8] found that the bellows have a unique buckling deformation due to their special shape and analyzed the buckling deformation and buckling criterion of bellows under pressure load.…”
Section: Introductionmentioning
confidence: 99%
“…M. Hamada [6] obtained information on the design of bellows through experimental studies and gave the appropriate design criteria. Mamtimin Geni [7] used a 1/4 finite element model based on the symmetry of the bellows and analyzed it under different numbers of diaphragm sets and loading conditions. K. Tsukimori [8] found that the bellows have a unique buckling deformation due to their special shape and analyzed the buckling deformation and buckling criterion of bellows under pressure load.…”
Section: Introductionmentioning
confidence: 99%